Planarization structure

CN122962881APending Publication Date: 2026-10-23CANATU OY
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202610411083.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-15
Filing Date
2026-03-31
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

尽管具有它们的优点,但是滤光器的性能可能因挑战(例如在高功率激光应用下的耐久性、热退化和制造公差)被限制

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122962881A_ABST
    Figure CN122962881A_ABST
Patent Text Reader

Abstract

The present application relates to planarized structures. A method for preparing a planarized structure consisting of a metal- or metalloid-containing coating between a first film of carbon nanostructures and a second film of carbon nanostructures is disclosed. The method comprises: - providing a first film of carbon nanostructures, - forming a planarization layer on the first film of carbon nanostructures by a solution-based deposition technique of a polymeric-based material to form a planarization layer on the first film of carbon nanostructures, - forming a metal- or metalloid-containing material on the planarization layer by a vapor deposition technique to form a planarized metal- or metalloid-containing coating on the planarization layer, - providing a second film of carbon nanostructures on the planarized metal- or metalloid-containing coating to form a pre-structure, - subjecting the formed pre-structure to a densification treatment; and removing the planarization layer from the pre-structure by a dissolution technique to prepare a planarized structure. The use of a planarized structure obtainable by the method is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to a method for preparing a planarized structure comprising a metal-containing or quasi-metal-containing coating between a first and a second carbon nanostructure. This disclosure also relates to the use of the planarized structure. Background Technology

[0002] Extreme ultraviolet lithography (EUV or EUVL) is an optical lithography technique that uses a specific range of extreme ultraviolet wavelengths. EUV protective films are used to protect photomasks from defects, improving accuracy, shortening processing time, and increasing wafer fabrication efficiency. However, defects in the printing process remain a key limiting factor for absorption in EUV lithography. Furthermore, filters are components designed to selectively transmit or block light of specific wavelengths. These filters play a role in applications such as spectroscopy, telecommunications, biomedical imaging, and photography. The materials and coating technologies used determine their performance, including spectral range, durability, and thermal resistance. Despite their advantages, filter performance can be limited by challenges such as durability under high-power laser applications, thermal degradation, and manufacturing tolerances. Problems such as surface defects, coating inconsistencies, or environmental factors (such as humidity) can introduce scattering or absorption losses, thereby reducing filtration efficiency and lifetime. Therefore, sophisticated particulate filters, such as EUV protective films or filters, are required. Summary of the Invention

[0003] This invention discloses a method for preparing a planarized structure, wherein the planarized structure comprises a metal-containing or quasi-metal-containing coating between a first film and a second film of a carbon nanostructure. The method includes: - Providing the first film with a carbon nanostructure, - A polymer-based material is formed on a first film of carbon nanostructures using a solution-based deposition technique to create a planarization layer on the first film of carbon nanostructures. - By using vapor deposition technology to form a planarized metal-containing or quasi-metal-containing material on the planarization layer, a planarized metal-containing or quasi-metal-containing coating is formed on the planarization layer. - A second film of carbon nanostructures is provided on the planarized metal-containing or quasi-metal-containing coating to form a prestructure. - The formed prestructure is densified, and - The planarization layer is removed from the prestructure using a dissolution technique to prepare the planarization structure.

[0004] The planarized structure, which can be obtained by the methods disclosed in this specification, is also disclosed for use as a filter, optical mirror, debris filter, protective film, filter membrane, electron blocking window, X-ray window, X-ray filter and X-ray filter mirror, or any combination of at least two of these. Attached Figure Description

[0005] The accompanying drawings, included to provide a further understanding of the embodiments and forming part of this specification, illustrate embodiments and, together with the description, help to explain the principles of the invention. In the drawings: Figure 1 An embodiment for preparing a planarized structure is shown.

[0006] Figure 2 The results for Example 2 are shown. Detailed Implementation

[0007] This disclosure relates to a method for preparing a planarized structure, the planarized structure comprising a metal-containing or quasi-metal-containing coating between a first film and a second film of a carbon nanostructure, wherein the method includes: - Providing the first film with a carbon nanostructure, - A polymer-based material is formed on a first film of carbon nanostructures using a solution-based deposition technique to create a planarization layer on the first film of carbon nanostructures. - By using vapor deposition technology to form a planarized metal-containing or quasi-metal-containing material on the planarization layer, a planarized metal-containing or quasi-metal-containing coating is formed on the planarization layer. - A second film of carbon nanostructures is provided on the planarized metal-containing or quasi-metal-containing coating to form a prestructure. - The formed prestructure is densified, and - The planarization layer is removed from the prestructure using a dissolution technique to prepare the planarization structure.

[0008] This disclosure also relates to the use of planarized structures obtainable by the methods disclosed in this specification as filters, optical mirrors, debris filters, protective films, filter membranes, electron blocking windows, X-ray windows, X-ray filters and X-ray filter mirrors, or any combination of at least two of these.

[0009] In one embodiment, the planarization structure is used as an extreme ultraviolet lithography protective film.

[0010] The planarized structure consists of a metal-containing or quasi-metal-containing coating between a first and a second film of a carbon nanostructure.

[0011] In one embodiment, the first and second films of the carbon nanostructure are self-supporting films of the carbon nanostructure or mesh-supporting films of the carbon nanostructure.

[0012] In this specification, the term "net" may refer to an interlaced structure. A net may serve as a support structure made of, for example, interwoven strands of metal.

[0013] Carbon nanostructures are used to form first and second films. Unless otherwise stated, the term "nanostructure" in this specification should be understood as a structure having one or more nanoscale feature sizes (i.e., typically 1 to 100 nm). The size of the nanostructure can be significantly different orders of magnitude in two perpendicular directions. For example, the length of the nanostructure can be ten, a hundred, a thousand, or even a hundred thousand times its thickness or width. In carbon nanostructure films, when carbon nanotubes are collected into a filter, a large number of said carbon nanostructures can interconnect with each other to form a network of interconnected molecules. Carbon nanostructures can also maintain an aligned or semi-aligned configuration, wherein individual nanostructures are vertically oriented when carbon nanotubes are harvested from the carbon nanotube array. The carbon nanotube array is a dense, vertically aligned array of carbon nanotubes. These structures can be grown on a substrate using techniques such as chemical vapor deposition. When fabricated into films, these structures can exhibit partial interconnection, forming a network, while retaining some of the alignment properties of the original array due to van der Waals forces or physical entanglement. As considered on a macroscopic scale, such networks form solid, monolithic materials in which the individual molecular structures are unoriented or non-oriented, that is, substantially randomly oriented. Various types of carbon nanostructure networks can be fabricated in the form of thin, transparent layers.

[0014] In one embodiment, the carbon nanostructure is a carbon nanotube (CNT), a carbon nanobud (CNB), a carbon nanoribbon, a carbon nanofiber, or any combination or mixture thereof. In another embodiment, the carbon nanostructure is a carbon nanotube, a carbon nanobud, or a combination or mixture thereof. Carbon nanobuds or carbon nanobud molecules may also be referred to as fullerenes or fullerene-like molecules having covalent bonds to the sides of tubular carbon molecules. Carbon nanotubes and carbon nanobuds themselves possess the added benefit of high transparency at X-ray and visible light wavelengths. Furthermore, they exhibit robust mechanical properties and high chemical inertness.

[0015] Various methods exist in the art for forming first and second films of carbon nanostructures. Different methods can be used to synthesize and / or deposit carbon nanostructures to form films. In the case of, for example, carbon nanotubes or carbon nanobud molecules, deposition can be performed, for example, by using methods commonly known to extract from solution through filtration from the gas phase or from a liquid, deposition in a force field, harvesting from carbon nanotube arrays, or deposition from solution using spraying or spin drying. Carbon nanobud molecules can be synthesized, for example, using the methods disclosed in WO2007 / 057501, and deposited directly onto a substrate from an aerosol stream, for example, by means of, electrophoresis or thermophoresis, or by deposition using the method described by Nasibulin et al., “Multifunctional Free-Standing Single-Walled 20 Carbon Nanotube Films” (ACSNANO, 2011, Vol. 5, No. 4, pp. 3214-3221). Functionalization of carbon nanostructures can be considered as the generation of functional groups on the surface of the carbon nanostructure. Functionalization of carbon nanostructures can be performed by physical adsorption or by covalent bonding. Functionalization of carbon nanostructures has the added benefits of making them more reactive, increasing their solubility, or allowing for various chemical modifications such as ion adsorption, metal deposition, or grafting reactions.

[0016] The first and / or second films of carbon nanostructures can be formed, for example, by synthesizing carbon nanostructures in the gas phase, from which the carbon nanostructures are collected or deposited. The carbon nanostructures can be collected or deposited to form films without a specific orientation, or they can be aligned in a specific direction.

[0017] The first and / or second films of carbon nanostructures can have a thickness of 0.1 to 1000 cm⁻¹. 2 or 1 to 500cm 2 or 5 to 350cm 2 or 10 to 200cm 2 or 50 to 150cm 2 Area dimensions.

[0018] The thickness of the first and / or second carbon nanostructure films can be 1 to 8000 nm, or 5 to 7500 nm, or 15 to 7000 nm, or 20 to 5000 nm, or 50 to 2500 nm, or 100 to 1000 nm, or 200 to 600 nm. In one embodiment, the thickness of the first and second carbon nanostructure films is 1 to 600 nm, or 15 to 500 nm, or 20 to 400 nm, or 50 to 300 nm, or 100 to 200 nm, or 75 to 100 nm. In another embodiment, the thickness of the first and second carbon nanostructure films is 100 to 8000 nm, or 200 to 7000 nm, or 300 to 5000 nm, or 400 to 2500 nm, or 500 to 1000 nm. The thicknesses of the first and second films of carbon nanostructures can be measured using contact surface photometry, such as atomic force microscopy (AFM), optical surface photometry, ellipsometry, or cross-sectional electron microscopy. The formation of the first and second films of carbon nanostructures has the added benefit of being able to form thin films. However, the first and second films of carbon nanostructures may not be too thin, as this would affect their ability to support themselves when forming self-supporting films. Conversely, when the films are supported by a mesh, the thicknesses of the first and second films can vary more freely.

[0019] The first and second films of carbon nanostructures can be self-supporting films or mesh-supporting films of carbon nanostructures. A self-supporting film is one that can exist independently without requiring a supporting substrate. A self-supporting film of carbon nanostructures can be self-supporting, meaning that the film has sufficient mechanical integrity and strength to independently maintain its structure. Self-supporting films can typically be formed directly as a freestanding entity, but they can also be fabricated as substrate-grown films to self-support after the substrate is removed. A defining characteristic of any self-supporting film is its ability to maintain its structure without a supporting substrate. Regardless of whether a self-supporting film is formed on a substrate, it can be considered self-supporting if it can exist and function independently after any processing steps (especially as described above). A self-supporting film does not need to be directly supported over its entire area because it can maintain its structure without direct support. It provides its own intrinsic structural support for maintaining its structure (e.g., its shape). This can be observed under gravity, in the absence of a supporting force on the self-supporting film. Therefore, the self-supporting films described herein can also be understood as self-supporting films.

[0020] A first and / or second membrane of the carbon nanostructure can be attached to a support. The support can be any type of support suitable for connection to the self-supporting membrane of the carbon nanostructure. The support can be formed of glass, metal, plastic, or any combination thereof. The form of the support can vary. The support can be in the form of a frame. In one embodiment, the support is in the form of a frame, and the membrane or carbon nanostructure is attached to the frame. The frame can support the self-supporting membrane of the carbon nanostructure at its outer edge, thereby forming an unsupported, independent region of the carbon nanostructure membrane. The support locations can be anywhere in the structure, as long as they provide sufficient support for the carbon nanostructure membrane. For example, they can be on the side of the self-supporting membrane of the carbon nanostructure, or in a region near a corner, or adjacent to each other along the side. For example, if the frame has a continuous circular shape (where the self-supporting region is located within the circle), any wider area including multiple support points also means being covered by that aspect. The frame can also have any other extended, continuous shape. In one embodiment, the frame is circular, square, triangular, rectangular, elliptical, or polygonal in shape.

[0021] Polymer-based materials are formed on carbon nanostructured films to create planarization layers. As used herein, the term "polymer-based material" can be used to refer to materials having a polymer content of 50 to 100% by weight. Examples of polymer-based materials used to form planarization layers include: organic polymers such as parylene and polyamides; naphthalene-containing polymers, oxygen-containing polymers such as polymethyl methacrylate (PMMA); hydrocarbon-based polymers consisting of carbon and hydrogen, such as polystyrene; oligomers such as short-chain polystyrene and oligomeric polyethylene glycol; solvent-processable fluorinated polymers such as polyvinylidene fluoride (PVDF) and polyolefins such as polypropylene, polyethylene, and polymethylpentene.

[0022] Polymer-based materials can be formed on a first film of carbon nanostructures using solution-based deposition techniques. Solution-based deposition techniques can be any general method in which a solution of coating is applied to the film by brushing, spraying, dipping, spreading, or dripping.

[0023] In one embodiment, the solution-based deposition technique is selected from spin casting, layer-by-layer deposition, spraying, electrophoretic deposition, Langmuir-Blodgett deposition, curtain coating, trench coating, or dip coating. These techniques are particularly advantageous for coating precision self-supporting CNT films because they typically apply lower mechanical stress compared to vacuum-based methods.

[0024] Using solution-based deposition techniques to form planarization layers has the added benefit of precisely controlling the thickness of the formed layer, allowing for layer thicknesses as low as tens of nanometers. It also allows for the efficient filling of any gaps between carbon nanostructures present in the film without the need for thick layers. In one embodiment, the solution-based deposition technique is dip coating. Using dip coating to form planarization layers has the added benefit of producing smooth, uniform, and defect-free coatings, which is beneficial for optical applications. Furthermore, the simplicity of setup and minimal equipment requirements make dip coating a cost-effective technique.

[0025] In one embodiment, the method includes forming a planarization layer having a thickness of 1 to 200 nm, or 5 to 180 nm, or 10 to 150 nm, or 20 to 100 nm, or 30 to 80 nm, or 40 to 60 nm. The thickness of the planarization layer can be measured using, for example, an electron microscope cross-section or X-ray reflectance.

[0026] The planarization layer has the added benefit of providing a smooth and uniform surface before the formation of a metallic or quasi-metallic coating. Any unevenness on the surface at this stage will be adversely replicated onto the metallic or quasi-metallic coating, thus affecting the final use of the structure.

[0027] After the planarization layer is formed, a metal-containing or quasi-metallic material is formed on the planarization layer using a vapor deposition technique to form a planarized metal-containing or quasi-metallic coating. As used herein, the term "metal-containing material" can be used to refer to a material containing a metal element or a metal compound. In one embodiment, the metal-containing material has a metal content of 50 to 100% by weight. In one embodiment, the quasi-metallic material has a quasi-metallic content of 50 to 100% by weight. Therefore, the planarized metal-containing or quasi-metallic coating can contain a total of 50 to 100% by weight of metal or quasi-metal. In one embodiment, the vapor deposition technique is selected from sputtering deposition, electron beam physical vapor deposition, thermal evaporation deposition, cathodic arc deposition, pulsed laser deposition, or ion beam-assisted deposition. Sputtering deposition uses plasma to eject material from a target and then deposit it onto the planarization layer. Electron beam physical vapor deposition uses a high-speed electron beam to evaporate the coating material, which then condenses onto the planarization layer. In thermal evaporation deposition, a resistance is used to heat the material to a high vapor pressure, causing it to deposit onto the planarization layer. In cathodic arc deposition, a high-power arc is used to evaporate the target material, which is then deposited onto a planarization layer. In pulsed laser deposition, a high-power laser ablates the material from the target, generating vapor that is deposited on the planarization layer. Ion beam-assisted deposition combines physical vapor deposition with simultaneous ion bombardment to improve film performance.

[0028] Using vapor deposition to form metallic or quasi-metallic coatings has the added benefit of creating thin coatings with smooth and uniform surfaces. Vapor deposition also offers the added benefit of providing precise nanoscale control over coating thickness, which is advantageous for EUV protective films.

[0029] In one embodiment, the metal-containing or quasi-metallic coating has a thickness of 1 to 1000 nm, 1 to 800 nm, 1 to 500 nm, 1 to 300 nm, 3 to 100 nm, 5 to 50 nm, 7 to 30 nm, 9 to 20 nm, or 10 to 15 nm. The thickness of the metal-containing or quasi-metallic coating can be measured using, for example, transmission electron microscopy (TEM), scanning electron microscopy (SEM), or any other relevant technique.

[0030] In one implementation, the metallic material is based on aluminum, zirconium, tungsten, niobium, titanium, yttrium, molybdenum, hafnium, vanadium, chromium, tantalum, scandium, gold, palladium, or lanthanum.

[0031] In one implementation, the quasi-metallic material is a boron- or silicon-based material.

[0032] The metal- or quasi-metallic coating may contain aluminum, zirconium, tungsten, niobium, titanium, yttrium, hafnium, vanadium, chromium, tantalum, scandium, gold, palladium, lanthanum, iron, nickel, cobalt, manganese, boron or molybdenum, or silicon, or any carbide, oxide, nitride, sulfide or boride thereof, or any combination or mixture thereof. The metal- or quasi-metallic coating may contain aluminum, zirconium, tungsten, niobium, silicon, titanium, yttrium, hafnium, vanadium, chromium, tantalum, scandium, gold, palladium, lanthanum, nickel, cobalt, manganese, boron or molybdenum, or any carbide, oxide, nitride, sulfide or boride thereof, or any combination or mixture thereof, or consist thereof. After forming the planarized metal- or quasi-metallic coating, a second film of carbon nanostructures is formed thereon.

[0033] After the prestructure is formed, it undergoes a densification process. In one embodiment, the densification process is vapor-phase densification, thermal annealing, electrostatic compression, or liquid impregnation densification. Densification processes have the added benefit of enhancing the mechanical strength, electrical conductivity, optical properties, and overall uniformity of the carbon nanostructure film. In one embodiment, vapor-phase densification is chemical vapor infiltration. In one embodiment, liquid impregnation densification is solvent-assisted densification. Liquid impregnation densification has the added benefit of eliminating the need for vacuum conditions and mechanical pressure, thus providing a gentler and warmer process.

[0034] In one embodiment, the vapor-phase densification process is carried out with a vapor-phase solvent at temperatures of 55 to 250°C, or 55 to 150°C, or 55 to 100°C, 55 to 75°C, or 60 to 70°C for 15 to 120 seconds, or 20 to 90 seconds, or 30 to 60 seconds. The solvent of the vapor phase can be isopropanol. The vapor-phase densification process can be carried out using a vapor-phase solvent (i.e., an evaporated solvent). The formed prestructure can be placed in a chamber where solvent vapor is introduced. The solvent vapor can then condense onto the prestructure, forming a thin liquid solvent film. The drying effect and surface tension of the solvent film can then pull the structures of the prestructure together to form a denser structure with higher mechanical strength. Densification of the prestructure has the additional benefit of coupling or bonding the carbon nanostructure film with a metal-containing or quasi-metal-containing coating to make them adhere to each other. Adhesion is maintained even under harsh conditions.

[0035] Following densification, the planarization layer is removed from the prestructure using a dissolution technique to prepare a planarized structure. When the planarization layer is removed to prepare the planarized structure, it serves as a sacrificial layer. In one embodiment, the dissolution technique is selected from wet chemical etching, dry etching, thermal decomposition, supercritical CO2 removal, electrochemical dissolution, solvent-based swelling and dissolution, or vapor phase etching. Dissolution techniques have the added benefit of being able to remove the planarization layer from the prestructure without eroding the film containing metal or quasi-metal coatings or carbon nanostructures. Wet chemical etching utilizes a liquid solvent or etchant to chemically react with the sacrificial layer, thereby selectively dissolving the sacrificial layer. Dry etching uses a reactive gas (plasma) to etch the sacrificial layer without using a liquid solvent. Thermal decomposition uses elevated temperatures to decompose the sacrificial layer. Supercritical CO2 removal utilizes supercritical carbon dioxide (CO2) as a solvent to remove the sacrificial layer in a controlled process. Electrochemical dissolution uses a voltage in a suitable electrolyte to etch the layer. Solvent-based swelling and dissolution uses a solvent to swell and dissolve the material. Vapor phase etching uses reactive vapor phase chemicals to selectively remove the sacrificial layer.

[0036] Increased exposed surface area can lead to higher oxidation, resulting in a loss of extreme ultraviolet (EUV) transmittance percentage. Therefore, planarized structures with less exposed area have the added benefit of minimizing oxidation, leading to a higher EUV transmittance percentage. Due to the smaller exposed area, there are also fewer pores, voids, or rough areas where dust or foreign particles can accumulate. This not only reduces the likelihood of contamination but also helps maintain the cleanliness and performance of the optical film over time. This is particularly important for optical films used in high-precision applications, as even small amounts of contaminants can degrade performance. Therefore, a smoother, less exposed surface makes it more difficult for contaminants to interact with the material, resulting in improved long-term stability and durability.

[0037] Example

[0038] Reference will now be made in detail to the described embodiments, examples of which are shown in the accompanying drawings.

[0039] The following description discloses in detail some embodiments that enable those skilled in the art to utilize methods based on this disclosure. Not all steps of the embodiments are discussed in detail, as some steps may be obvious to those skilled in the art based on this specification.

[0040] Figure 1 An embodiment for preparing a planarized structure as disclosed in this specification is shown.

[0041] First, a first film of carbon nanostructures is provided. This first film of carbon nanostructures can be formed, for example, by a gas-phase method, wherein the carbon nanostructures are, for example, carbon nanotubes (in...). Figure 1 Carbon nanostructures (CNTs) are synthesized in the gas phase and then deposited or collected on a substrate such as a porous filter. The resulting carbon nanostructure membrane can be peeled off from the substrate and transferred to a support such as a frame.

[0042] Then, a polymer-based material is formed on the first film of carbon nanostructures (CNTs) using a solution-based deposition technique. Figure 1 (labeled as PMMA) to form a planarization layer on the first film of carbon nanostructures.

[0043] Then, a metal-containing or quasi-metal-containing material is formed on the planarization layer (PMMA) using vapor deposition technology. Figure 1 (marked as metal) to form a planarized metal-containing or quasi-metal-containing coating on the planarization layer.

[0044] Then, a second film of carbon nanostructures (labeled CNTs) is provided on a planarized metal-containing or quasi-metal-containing coating (metal) to form a prestructure.

[0045] These steps are followed by densification of the formed prestructure, and then the planarization layer is removed from the prestructure using a dissolution technique to prepare the planarization structure. Therefore, the planarization structure is formed by a metal-containing or quasi-metal-containing coating between a first and a second carbon nanostructure film.

[0046] Example 1 - Fabrication of Planarized Structures

[0047] In this example, a planarized structure was prepared. The materials used are shown in Table 1.

[0048] Table 1. Materials used for preparing planarization structures Circular frame, 21mm inner diameter, 37mm outer diameter First, carbon nanotubes were synthesized in an aerosol laminar flow (floating catalyst) reactor using carbon monoxide and ferrocene as carbon source and catalyst precursor, respectively. The formed carbon nanotubes were deposited from the gas phase onto a porous collection filter at a total gas flow rate of 60 L / min (maximum gas velocity 0.13 m / s) to form a carbon nanotube film on the filter. The gas temperature was approximately 60 °C. The thickness of the first carbon nanotube film formed was 50 nm, corresponding to 81%T at a wavelength of 550 nm.

[0049] The resulting first membrane of carbon nanotubes is then transferred from the porous collection filter to a rectangular plastic frame larger than the final circular frame. This frame is then transferred onto the final circular frame to form a self-supporting membrane of carbon nanotubes attached to the frame. Therefore, the frame has a circular shape with an opening in the center.

[0050] Subsequently, a polymer-based material was deposited onto a first film of carbon nanotubes via dip coating, wherein the dip coating dip-and-remove rate was 25 mm / min. After dip coating, the film was dried in a ventilated oven at 100°C for 15 minutes. In this example, PMMA was used as the polymer-based material.

[0051] Then, a metallized Au / Pd alloy coating was formed on the planarization layer using physical vapor deposition. In this case, sputtering deposition was performed using argon plasma (base pressure 1E-5 mbar, operating pressure 1E-2 mbar, deposition rate approximately 10 nm / min, unheated sample, and the sputtering target was pre-cleaned for 1 minute prior to deposition to remove native oxides). The thickness of the metallized coating was 50 nm.

[0052] Then, a film of carbon nanotubes prepared as described above is formed on the metal coating.

[0053] Then, the prestructure was vapor-densified by placing it in the chamber for 60 seconds, and isopropanol vapor was introduced into the chamber at a temperature of 66°C.

[0054] Following vapor-phase densification, the planarization layer was removed from the prestructure using a dissolution technique. The film was then immersed in acetone at 50°C for 1 hour, using the same immersion and removal parameters as those used for PMMA deposition.

[0055] Example 2 - Fabrication of planarized structures

[0056] In this example, the planarized structure was prepared and tested. The materials used are shown in Table 2.

[0057] Table 2. Materials used for preparing planarization structures

[0058] First, carbon nanotubes were synthesized in an aerosol laminar flow (floating catalyst) reactor using carbon monoxide and ferrocene as carbon source and catalyst precursor, respectively. The formed carbon nanotubes were deposited from the gas phase onto a porous collection filter at a total gas flow rate of 60 L / min (maximum gas velocity 0.13 m / s) to form a carbon nanotube film on the filter. The gas temperature was approximately 60 °C. The thickness of the first carbon nanotube film formed was 50 nm, corresponding to 81%T at a wavelength of 550 nm.

[0059] The resulting first membrane of carbon nanotubes is then transferred from the porous collection filter to a rectangular plastic frame larger than the final circular frame. This frame is then transferred onto the final circular frame to form a self-supporting membrane of carbon nanotubes attached to the frame. Therefore, the frame has a circular shape with an opening in the center.

[0060] Subsequently, a polymer-based material was deposited onto a first film of carbon nanotubes via dip coating, wherein the dip coating dip-and-remove rate was 25 mm / min. After dip coating, the film was dried in a ventilated oven at 100°C for 15 minutes. In this example, PMMA was used as the polymer-based material.

[0061] A Zr-containing metallized coating was then formed on the planarization layer using physical vapor deposition. In this case, sputtering deposition was performed using argon plasma (base pressure 1E-5 mbar, operating pressure 5, 3E-3 mbar, deposition rate approximately 1.83 m / sec (11 nm / min), unheated sample, and the sputtering target was pre-cleaned for 1 minute prior to deposition to remove native oxides). The thickness of the metallized coating was 50 nm.

[0062] Then, a film of carbon nanotubes prepared as described above is formed on the metal coating.

[0063] Then, the prestructure was vapor-densified by placing it in the chamber for 60 seconds, and isopropanol vapor was introduced into the chamber at a temperature of 66°C.

[0064] Following vapor-phase densification, the planarization layer was removed from the prestructure using a dissolution technique. The film was then immersed in acetone at 50°C for 1 hour, using the same immersion and removal parameters as those used for PMMA deposition.

[0065] The planarized structure was measured using EUV measurements with a particle accelerator (synchrotron). The results are shown in... Figure 2 middle.

[0066] Example 3 - Testing the flattened structure

[0067] In this example, a planarized structure prepared according to the description in Example 2 is tested and compared with a sample in which a metal coating is formed directly on the carbon nanotube film without using a planarization layer.

[0068] The formed sample was measured using EUV accelerator (synchrotron). The results are shown below. Figure 2 middle.

[0069] The results show that when a planarized structure is prepared, i.e., when a planarization layer of a polymer-based material with a zirconium coating is used, the visible light transmittance is about 7.5%, while when the same material is formed directly on a carbon nanostructure film without using a planarization layer of a polymer-based material, the visible light transmittance is about 14.8%.

[0070] It can be concluded that the difference in visible light transmittance is caused by pinholes in the porous film of carbon nanotubes, which is the opposite of the case where a zirconium-containing coating is formed on a planarization layer, which makes the surface continuous and ideally free of pinholes.

[0071] Furthermore, it was concluded that when zirconium-containing coatings are formed directly on porous films of carbon nanotubes, oxidation occurs due to the disordered morphology, which translates into increased chemical reactivity.

[0072] It will be apparent to those skilled in the art that the basic idea can be implemented in various ways as technology advances. Therefore, the embodiments are not limited to the examples described above; rather, they may vary within the scope of the claims.

[0073] The embodiments described above can be used in any combination of each other. Several embodiments can be combined together to form another embodiment. The methods, structures, or uses disclosed herein may include at least one of the embodiments described above. It should be understood that the above benefits and advantages may relate to one embodiment or several embodiments. These embodiments are not limited to those embodiments that solve any or all of the described problems or those embodiments that have any or all of the described benefits and advantages. It should also be understood that reference to "a" means one or more of these items. The term "comprising" is used in this specification to mean including the feature or action that follows it, without excluding the presence of one or more additional features or actions.

Claims

1. A method for preparing a planarized structure, said planarized structure comprising a metal-containing or quasi-metal-containing coating between a first film and a second film of a carbon nanostructure, wherein, The method includes: - Providing the first film with a carbon nanostructure, - A polymer-based material is formed on the first film of carbon nanostructure using a solution-based deposition technique to form a planarization layer on the first film of carbon nanostructure. - A metal-containing or quasi-metal-containing material is formed on the planarization layer using vapor deposition technology to form a planarized metal-containing or quasi-metal-containing coating on the planarization layer. - A second film of carbon nanostructures is provided on the planarized metal-containing or quasi-metal-containing coating to form a prestructure. - The formed prestructure is densified, and - The planarization layer is removed from the prestructure using a dissolution technique to prepare the planarization structure.

2. The method according to claim 1, wherein, The first and second films of the carbon nanostructure are self-supporting films or network-supported films of the carbon nanostructure.

3. The method according to any one of the preceding claims, wherein, The polymer-based material is polymethyl methacrylate.

4. The method according to any one of the preceding claims, wherein, The metal-containing material is based on aluminum, zirconium, tungsten, niobium, titanium, yttrium, molybdenum, hafnium, vanadium, chromium, tantalum, scandium, gold, palladium, lanthanum, iron, nickel, cobalt, or manganese.

5. The method according to any one of the preceding claims, wherein, The quasi-metallic material is based on silicon or boron.

6. The method according to any one of the preceding claims, wherein, The method includes forming a metal-containing or quasi-metal-containing coating with a thickness of 1 to 1000 nm, 1 to 800 nm, 1 to 500 nm, 1 to 300 nm, 3 to 100 nm, 5 to 50 nm, 7 to 30 nm, 9 to 20 nm, or 10 to 15 nm.

7. The method according to any one of the preceding claims, wherein, The solution-based deposition technique is selected from rotary casting, layer-by-layer deposition, spraying, electrophoretic deposition, Langmuir-Blodgett deposition, curtain coating, trench coating, or dip coating.

8. The method according to any one of the preceding claims, wherein, The vapor deposition technique is selected from sputtering deposition, electron beam physical vapor deposition, thermal evaporation deposition, cathode arc deposition, pulsed laser deposition, or ion beam assisted deposition.

9. The method according to any one of the preceding claims, wherein, The densification process is vapor-phase densification, thermal annealing, electrostatic compression, or liquid impregnation densification.

10. The method according to any one of the preceding claims, wherein, The dissolution technology is selected from wet chemical etching, dry etching, thermal decomposition, supercritical CO2 removal, electrochemical dissolution, solvent-based swelling and dissolution, or vapor phase etching.

11. Use of a planarization structure, said planarization structure being obtainable by any one of claims 1 to 10, said planarization structure being used as a filter, optical mirror, debris filter, protective film, filter membrane, electron blocking window, X-ray window, X-ray filter and X-ray filter mirror, any combination of at least two of these.

12. The use according to claim 11, wherein, The planarization structure is used as a protective film for extreme ultraviolet lithography.

Citation Information

Patent Citations

  • Carbon nanotubes functionalized with fullerenes

    WO2007057501A1